Dynamic performance of high supporting formwork under horizontal impact load. (9th December 2019) - Lu, Zhengran; Zhang, Maosheng; Guo, Chao
Dynamic performance of a high full-scale supporting formwork (HSF) subjected to horizontal impact loading was examined. It could be concluded that transverse X-bracings in the horizontal impact load direction have a more significant effect on the bearing performance and dynamic characteristics of an HSF than longitudinal X-bracings. An increase in the amount of poured concrete and the failure of the X-bracings reduces the natural frequency of the HSF. With the gradual increase in the amount of poured concrete, the maximum dynamic axial force of posts may increase from 4.33 kN to 12.77 kN under different X-bracing conditions during concrete placement. With failure of some main nodes, any impact load significantly increases the axial force acting on the posts. Dynamic axial force acting on some of the posts can increase by as much as 120% if 5% of fasteners fail during concrete pouring compared with that when all fasteners and X-bracings are intact.